PENGGUNAAN PROGRAM CPCe (CORAL POINT COUNT WITH EXCEL EXTENSIONS) UNTUK MENGETAHUI KONDISI TERUMBU KARANG DI PERAIRAN SEKITAR PULAU BATAMPENGGUNAAN PROGRAM CPCe (CORAL POINT COUNT WITH EXCEL EXTENSIONS) UNTUK MENGETAHUI KONDISI TERUMBU KARANG DI PERAIRAN SEKITAR PULAU BATAM - Ramadhani, Anindyta Fitria; Luthfi, Oktiyas Muzaky (JFMR (Journal of Fisheries and Marine Research), 2019)
A healthy coral reef ecosystem will be used as a place for spawning and foraging for various marine biota. With high primary productivity and diversity, coral reef ecosystems will become ecosystem that has a lot of useful potential. Abang Island and Abang Besar Island, Batam, are two of the locations with a good coral reef ecosystem. Unfortunately, these ecosystems have been disturbed by marine tourism activities. Therefore, observations are needed to determine the condition of coral reefs in Abang and Abang Besar Islands. Coral Point Count with Excel Extensions (CPCe) is a software that helps to identify and know the condition of coral reefs in an area. Data processing in this CPCe program will generate data in the form of Excel files that show the results of identification analysis. Based on data processing using the CPCe program, the results of the percentage of coral cover at the six stations varied (32.67 - 51.33%) from the bad to good categories. At Station 1 or BTMC01, the highest coral cover is 51.33% and the lowest is at Station 2 or BTMC02 at 32.67%. The condition of coral reefs with good categories is only found in BTMC01, the rest has the condition of coral reefs in the medium category. The percentage of coral cover obtained is a combination of Acropora and Non-Acropora coral group species. Good or bad coral cover in an area is strongly influenced by anthropogenic activities.